Mesenchymal Stem and Progenitor Cells in Regeneration: Tissue Specificity and Regenerative Potential - Rokhsareh Rohban; Thomas Rudolf Pieber (Stem Cells International)
It has always been an ambitious goal in medicine to repair or replace morbid tissues for regaining the organ functionality. This challenge has recently gained momentum through considerable progress in understanding the biological concept of the regenerative potential of stem cells. Routine therapeutic procedures are about to shift towards the use of biological and molecular armamentarium. The potential use of embryonic stem cells and invention of induced pluripotent stem cells raised hope for clinical regenerative purposes; however, the use of these interventions for regenerative therapy showed its dark side, as many health concerns and ethical issues arose in terms of using these cells in clinical applications. In this regard, adult stem cells climbed up to the top list of regenerative tools and mesenchymal stem cells (MSC) showed promise for regenerative cell therapy with a rather limited level of risk. MSC have been successfully isolated from various human tissues and they have been shown to offer the possibility to establish novel therapeutic interventions for a variety of hard-to-noncurable diseases. There have been many elegant studies investigating the impact of MSC in regenerative medicine. This review provides compact information on the role of stem cells, in particular, MSC in regeneration.